UNIVERSAL PRECAUTION KNOWLEDGE LEVELS IN POSTGRADUATE STUDENTS FACULTY OF DENTISTRY - Sri Sarwendah; Syarif Suwondo; Irena Nisa Harliani (Fakultas Kedokteran Gigi Unjani, 2021)
Universal precautions are one way to prevent the transmission of disease, which is transmitted by blood and all body fluids, including saliva, either from the patient to health worker and from patient to another patient. Patients should be treated as infected with the disease and potentially infectious every time. This action should be done by all health care staff in the risk of cross-infection between patients, and health workers can be minimized. Basic universal precautions include immunization, hand washing, personal protective equipment, medical equipment management, and hospital waste management. This study aims to describe the level of knowledge about universal precautions in clerkship student of the Dentistry Faculty of Unjani. This study used a descriptive design by cross- sectional. Collection data for research using a questionnaire containing 20 questions tested for validity and reliability, then a questionnaire filled out by respondents as many as 40 people. Presentation of research data is processed and presented to illustrate the level of knowledge in clerkship of frequency distribution table. The results showed that most of the clerkship has a high knowledge (60%), a clerkship with a moderate level of knowledge (27,5%), and a clerkship with the knowledge that a low level (12,5%). Conclusions of the research show that the majority of clerkship student of Dentistry of Medical Unjani about universal precaution is at a high level (60%). DOI : 10.54052/jhds.v1n1.p71-79